The role of bio-additive and attractive magnetic fields on flame behavior and hydrocarbon gas in palm oil droplets combustion - Dony Perdana; Mochammad Khoirul Rosidin; Wahyu Dwi Purnama (Universitas Gadjah Mada, 2025)
The availability of fossil fuels is increasingly diminishing, while the global energy demand continues to rise. Alternative energy sources currently available from various vegetable oils include jatropha, palm, kapok seed, coconut, and cottonseed oil as substitutes for fossil fuels. When used directly in diesel engines, these oils can lead to several issues, including high viscosity and elevated flash points, which hinder proper fuel combustion and result in carbon deposits within the combustion chamber. Several solutions have been proposed to address these issues, including blending vegetable oils with diesel fuel at various ratios, preheating the vegetable oils, mixing them with additives, and utilizing exhaust gas recirculation and combustion chamber modification. This study investigates the role of bio-additive and applied magnetic fields in influencing flame characteristics and hydrocarbon gas emissions during palm oil droplet combustion. The experimental procedure involved direct testing on palm oil by incorporating a 3% eucalyptus oil-based bio additive and applying an attractive magnetic field (U-S), with droplet diameters ranging between 0.3-0.4 mm. Thermocouples diameter of 0.12 mm were placed on both sides of the magnet with a magnetic field intensity of 1.1 Tesla, and heating wires as the heat source were positioned beneath the thermocouples. The study found that combining eucalyptus oil bio-additive and an attractive magnetic field (U-S) resulted in the shortest flame evolution time of 1760 ms. The flame height and hydrocarbon gas concentration also reached their lowest values at 5.74 mm and 296 ppm, respectively. Meanwhile, the same treatment produced of highest temperature of 846.5 °C compared to other experimental conditions.